2007
DOI: 10.1021/jm0701021
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Targeted Prodrugs of 2‘-C-Methyladenosine for Therapy of Hepatitis C Virus Infection

Abstract: 2'-C-Methyladenosine exhibits impressive inhibitory activity in the cell-based hepatitis C virus (HCV) subgenomic replicon assay, by virtue of intracellular conversion to the corresponding nucleoside triphosphate (NTP) and inhibition of NS5B RNA-dependent RNA polymerase (RdRp). However, rapid degradation by adenosine deaminase (ADA) limits its overall therapeutic potential. To reduce ADA-mediated deamination, we prepared cyclic 1-aryl-1,3-propanyl prodrugs of the corresponding nucleoside monophosphate (NMP), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Finally, it was found that the use of t- BuMgCl on 2′,3′-protected nucleosides resulted in the exclusive formation of cis -isomers as illustrated in Scheme 70 with cytarabine (52%) 99 and 2′-Me-A (35%). 101 Determination of the stereochemistry of the final product was established by comparison of NMR data with literature examples. Isopropylidene and TBS protective groups were finally removed after phosphorylation under acidic condition or by treatment with a source of fluorine (TEAF, TBAF).…”
Section: Nucleoside Monophosphate Prodrugsmentioning
confidence: 99%
“…Finally, it was found that the use of t- BuMgCl on 2′,3′-protected nucleosides resulted in the exclusive formation of cis -isomers as illustrated in Scheme 70 with cytarabine (52%) 99 and 2′-Me-A (35%). 101 Determination of the stereochemistry of the final product was established by comparison of NMR data with literature examples. Isopropylidene and TBS protective groups were finally removed after phosphorylation under acidic condition or by treatment with a source of fluorine (TEAF, TBAF).…”
Section: Nucleoside Monophosphate Prodrugsmentioning
confidence: 99%
“…There was a substantial increase in mice, compared to the non-phosphorylated AraC as a control. The HepDirect technology also was applied to a 2′,3′-carbonate to make an orally available compound (39%) with high liver potency [81,82]. …”
Section: Ester Prodrugsmentioning
confidence: 99%
“…Since it was hypothesized that preparation of a 5′-monophosphate prodrug would block deamination and increase therapeutic levels of 2′-C-methyladenosine triphosphate (10) in the liver, a HepDirect prodrug approach was investigated. An SAR study evaluated activation in rat hepatocytes by modifications to the aryl substituent of the HepDirect prodrug moiety [108]. This assessment showed that the prodrugs were generally efficiently cleaved and converted to the nucleoside triphosphate 10 ( Figure 6) particularly those with halogen substituted phenyl 51 or pyridyl groups ( Figure 19).…”
Section: ′-C-methyladenosine Hepdirect Prodrugsmentioning
confidence: 99%